Current knowledge on irritable bowel syndrome treatment - literature overview - Jasiuk, Ilona; Chrościński, Kamil; Łukaszewska, Ewa; Sajkiewicz, Ilona; Miga-Orczykowska, Nadia; Lemieszek, Paulina; Wójtowicz, Justyna; Krukar, Katarzyna; Pustelniak, Martyna; Kister, Klaudia; et al. (Journal of Education, Health and Sport, 2024)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder characterized by symptoms such as abdominal pain, bloating, and altered bowel habits. It affects a large proportion of the general population leading to a negative effect on the quality of life. The pathophysiology of IBS is not fully known. There are several therapies currently used in the treatment of IBS. They vary from changing dietary habits to antibiotic therapy and must be personalized.